Uznanie ojcostwa nowym sposobem ustalenia pochodzenia dziecka - Pietrzak, Helena (Prawo Kanoniczne, 2009)
On 13th June 2009 the amending of the family and guardianship code became effective, which thoroughly reformed the issues of a child’s descent, an aspect of parental authority and significantly influences a change of financial relations and situation in a family. One of the most essential changes is introduction of the institution of “acknowledgment of paternity” instead as so far a declaration on being a child’s father. It applies to the situation when there is no presumption that a husband of the child’s mother is the child’s father or when such presumption is destroyed. Thus the identification of paternity may come through acknowledgment of paternity or by decision of a court. The essence of changes in this regard is a possibility of effective expression of an act of acknowledgment by a biological father having a limited capacity to legal transaction (a requirement of the age of 16) without consent of his legal representative (exclusively before a guardianship court; if there are no grounds for his complete legal incapacitation). Such changes shall undoubtedly result in acceleration of all procedure of acknowledgment, since previously legal representatives of a minor could effectively obstruct going through such formalities owing to financial implications (e.g. child support). Time limits for a mother for confirmation of a declaration on acknowledgement of paternity remain unchanged. The amending of the family and guardianship code introduced also a few changes in acknowledgment of paternity by a minor father who can make a declaration (a strictly personal act) before the superintendent registrar and a child’s mother is to confirm at the same time or within three months of the date of the man’s declaration that such man is the child’s father. Besides, the acknowledgment of paternity may occur before a guardianship court and if abroad, also before a Polish consul or a person appointed to perform functions of a consul, if the acknowledgment concerns a child whose both or one of parents is a Polish citizen (art. 73 § 4 of the family and guardianship court). A catalog of persons entitled to take a declaration in circumstance of a threat to life has also been broadened. Subject to art. 74 § 1 of the family and guardianship code in case of any danger directly threatening life of a child’s mother or a man, whom the child descends from, a declaration necessary for acknowledgment of paternity may be recorded by a notary public or to made on record before a head of a commune (a mayor, a president of a town), a chief official of a district, a governor of a province, a secretary of a district or a commune. The record including the declaration necessary for acknowledgment of paternity should be immediately submit to the registrar’s office competent for preparation of a birth certificate of the child.